Sealability of MTA and calcium hydroxidecontaining sealers - João Eduardo Gomes-Filho; Jaqueline Viana Moreira; Simone Watanabe; Carolina Simonetti Lodi; Luciano Tavares Angelo Cintra; Eloi Dezan Junior; Pedro Felício Estrada Bernabé; Mauro Juvenal Nery; José Arlindo Otoboni Filho (University of São Paulo, 2012)
OBJECTIVES: The aim of this study was to evaluate the apical sealability of Fillapex®, endo-CPM-Sealer® and Sealapex®. Material and Methods: Ninety-four freshly extracted single-rooted teeth were selected and decoronated. All teeth were radiographed to confirm the existence of a single and straight root canal, which was prepared using Protaper Universal and 2.5% sodium hypochlorite. The teeth were randomly divided in groups of 10 specimens each according to the sealer, and the canals were filled using the single cone technique and one of the sealers. Four additional teeth were used as controls. The teeth were submitted to dye leakage with Rhodamine B for 24 h but using vacuum on the initial 15 min. Thereafter, they were cut longitudinally and the leakage was measured in a linear fashion from apex to crown. Data were analyzed by ANOVA and Tukey's tests at 5% significance level. Results: Fillapex® and Sealapex® showed significantly less dye leakage than endo-CPM-Sealer® (p<0.05). Conclusions: It was concluded that Fillapex® and Sealapex® were able to prevent apical dye leakage differently from endo-CPM-Sealer®.